Do Acupuncture Services Reduce Subsequent Utilization of Opioids and Surgical Interventions Compared to Noninvasive Therapies among Patients with Pain Conditions?. Issue 11 (15th June 2021) - Pham, Timothy; Ma, Qinli; Agiro, Abiy; Bukowiec, Julie; Flannery, Terry
Abstract: Objective: To compare prescribed opioid use and invasive surgical interventions between patients using acupuncture and those using non-steroidal anti-inflammatory drugs (NSAIDs)/physical therapy (PT). Design: Retrospective observational study of administrative claims. Setting: Large commercial insurance plan. Subjects: 52 346 each treated with either acupuncture or NSAIDs/PT. Methods: Users of acupuncture and NSAIDs/PT were identified from January 1, 2014, to December 31, 2017. The first date of each service was defined as the index date. Acupuncture patients were 1:1 propensity score matched to the NSAIDs/PT group on baseline characteristics. Outcomes included opioid use, subsequent invasive surgical procedures, healthcare utilization such as hospitalizations or emergency department (ED) visits, and costs. These were assessed in the 12-month period before index date (baseline) and 12-month period following index date (follow-up) using difference-in-difference (DID) analysis. Results for opioid use were stratified by those with and without baseline opioid use. Results: The acupuncture group had fewer patients initiating opioids post-index both among those with (49.2% vs 56.5%, P  < .001) and without (15.9% vs 22.6%, P  < .001) baseline opioid use. There was a small increase in invasive surgical procedures with acupuncture (3.1% vs 2.8%, P  = .006). A reduction in ED visits was observed with acupuncture (DID −4.6% for all-cause; −3.3% for pain-related, all P  < .001). Acupuncture was associated with higher total medical and pharmacy costs (DID +$1331 per patient, P  = .006). Conclusions: Acupuncture showed a modest effect in reducing opioid use and ED visits. More research on acupuncture's place in emergency care, pain relief, and comparison to other types of non-opioid treatment is needed.